Endoscopic Surveillance in Inflammatory Bowel Diseases: Selecting a Suitable Technology - Dal Buono, Arianna; Gabbiadini, Roberto; Furfaro, Federica; Argollo, Marjorie; Trigo, Thaís Viana Tavares; Repici, Alessandro; Roda, Giulia (Frontiers in Medicine, 2022)
In the treat-to-target era, endoscopy has become the backbone of the assessment of remission, defined as mucosal healing, in inflammatory bowel disease (IBD) patients. Current recommendations indicate that endoscopic procedures should be performed with high-definition white-light endoscopy (HD-WLE), as it guarantees the best possible visualization of the mucosa. With respect to endoscopic surveillance, the preventive strategy for dysplasia and colorectal cancer (CRC) in long-standing IBD, the use dye-chromoendoscopy (DCE), that enhances the mucosal pattern of the colonic walls, has been established as the gold standard for dysplasia detection and is at present incorporated in all international guidelines. In the last years, novel technologies, such as high-definition endoscopic imaging, optical and digital enhancement tools have revolutionized the quality and level of fine details of vascular and mucosal pattern. These endoscopic images have the ambition to reflect histological changes for suspected neoplastic lesions and inflammation or healing and are emerging as potential alternatives to DCE. Indeed, the comparison of DCE with high-definition imaging is an open issue that deserves further investigation. We aimed to examine and summarize the technical aspects and the current evidence on endoscopic technologies with a specific focus on the surveillance in IBD patients.